Dynamics of Translocation and Substrate Binding in Individual Complexes Formed with Active Site Mutants of Φ29 DNA Polymerase - Dahl, Joseph M. (American Society for Biochemistry and Molecular Biology, 2014)
The Φ29 DNA polymerase (DNAP) is a processive B-family replicative DNAP. Fluctuations between the pre-translocation and post-translocation states can be quantified from ionic current traces, when individual Φ29 DNAP-DNA complexes are held atop a nanopore in an electric field. Based upon crystal structures of the Φ29 DNAP-DNA binary complex and the Φ29 DNAP-DNA-dNTP ternary complex, residues Tyr-226 and Tyr-390 in the polymerase active site were implicated in the structural basis of translocation. Here, we have examined the dynamics of translocation and substrate binding in complexes formed with the Y226F and Y390F mutants. The Y226F mutation diminished the forward and reverse rates of translocation, increased the affinity for dNTP in the post-translocation state by decreasing the dNTP dissociation rate, and increased the affinity for pyrophosphate in the pre-translocation state. The Y390F mutation significantly decreased the affinity for dNTP in the post-translocation state by decreasing the association rate ∼2-fold and increasing the dissociation rate ∼10-fold, implicating this as a mechanism by which this mutation impedes DNA synthesis. The Y390F dissociation rate increase is suppressed when complexes are examined in the presence of Mn(2+) rather than Mg(2+). The same effects of the Y226F or Y390F mutations were observed in the background of the D12A/D66A mutations, located in the exonuclease active site, ∼30 Å from the polymerase active site. Although translocation rates were unaffected in the D12A/D66A mutant, these exonuclease site mutations caused a decrease in the dNTP dissociation rate, suggesting that they perturb Φ29 DNAP interdomain architecture.